MOLECULAR DYNAMICS SIMULATION-BASED STUDY OF PROTEIN-LIGAND INTERACTIONS IN DRUG DESIGN - Amirkulova Sug‘diyona Shokir qizi; Dilmurodova Fayyoza; Boboqulova O. S. (Modern American Journals, 2026)
Protein–ligand interactions are essential determinants of therapeutic efficacy, guiding the rational design of novel drugs. This study focuses on a heterocyclic inhibitor targeting the ATP-binding pocket of human tyrosine kinase. Molecular docking and 100 ns molecular dynamics (MD) simulations were performed to investigate the ligand’s binding stability, interaction mechanisms, and energetic profile. Key parameters including root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), radius of gyration (Rg), solvent-accessible surface area (SASA), hydrogen bond occupancy, and binding free energy using MM-PBSA were analyzed. The ligand demonstrated stable binding, persistent hydrogen bonding with catalytic residues Glu85, Asp142, and Lys89, and favorable binding free energy (ΔG = −42.6 kcal/mol). Structural analysis confirmed minimal perturbation of the protein backbone, preserved compactness, and maintained solvent exposure. The ligand also satisfies Lipinski’s rule-of-five, indicating potential drug-likeness. These findings highlight the utility of MD simulations combined with free energy calculations for rational drug design, providing mechanistic insights and guiding further preclinical development.
Keywords: Molecular dynamics, protein–ligand interaction, docking, MM-PBSA, tyrosine kinase, drug design.